PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) OFF GRID DI PT. GEBER SAMUDRA - Aji Wicaksono, Suryo; Sari Hartati, Rukmi; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 10 No 3 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i03.p8, 2023)
Indonesia has a great opportunity to utilize new renewable energy sources for conversion to electric power. One possible use of renewable energy is solar power plants (PLTS). The average potential of solar energy in Indonesia is around 4.8 kWh/m2/day. Therefore, this study is related to the design of PLTS on the roof of PT. Geber Samudra is off the grid. The design of this solar power plant is made with the help of Helioscope software with a total roof area of 125.71 m2 and a roof slope of 20°. The potential power generated is 9.8 kWp and the total annual energy production is 15.56 MWh. It takes 28 pieces of UKSOL UKs-6M 350wp solar panels, 1 Solax X3 HYBRID 10.0 T type inverter with a capacity of 10 kW, and 6 units of 48V 100Ah batteries assembled in series. Based on the results of PLTS roof design can be analyzed that the planning of PLTS roof at PT. Geber Samudra is considered worthy because it meets the criteria of net present value (NPV) of Rp. 25.603.062 is greater than zero. The Benefit-Cost Ratio (B-CR) is greater than one which is 1.12, and the discounted payback period (DPP) is 21,8 years and is achieved at the age of PLTS with the assumption of operating for 25 years.